A&T Ethiopia Complementary Feeding Endline Survey 2017: Health Development Army Team Leaders - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the health development army team leaders (HDATL) survey that was conducted to gather data at endline as part of the study assessing the impact of the A&T social and behavior change communication (SBCC) interventions in the Amhara region of Ethiopia. A&T is a global initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding and complementary feeding practices. A&T's focus in this phase of the study in Ethiopia (with program implementation from late 2014 to 2017) is on operationalizing the IYCF component of the Government of Ethiopia’s National Nutrition Plan (NNP) in one region, Amhara. The objectives of the A&T initiative in Amhara are as follows: 1) Sustain high rates of EBF among children 0–5.9 months at over 70 percent in A&T program areas, 2) Increase the proportion of children 6–23.9 months of age who receive a diverse diet (at least four food groups) by 10 percentage points in A&T program area, and 3) Increase the proportion of breastfed and non-breastfed children 6–23.9 months of age who receive solid, semi-solid, or soft foods at least the minimum number of times per day by 10 percentage points in A&T program areas. A cluster-randomized design with repeated cross-sectional surveys at baseline (2015) and endline (2017) were used to assess impact of the A&T social and behavior change communication (SBCC) interventions in Amhara region, particularly the community-based interventions (interpersonal communication and social mobilization) and mass media activities. The evaluation includes household and frontline worker (FLW) surveys. Twenty woredas (districts) were purposively selected as potential areas of work by A&T HQ and Save the Children, and the select woredas were randomly assigned as 10 intervention (or A&T-intensive, A&T-I) and 10 comparison (or A&T-Non intensive, A&T-NI) woredas. The endline survey applied 5 questionnaires that aimed to capture elements along the program impact pathways: (1) household questionnaire and anthropometric measurements of children and mothers, (2) community questionnaire, (3) frontline worker questionnaire: Health extension worker (HEW), (4) Frontline worker questionnaire: Health development army team leader (HDATL), and (5) Frontline worker questionnaire: Agriculture development agent (ADA). A household roster was used to gather information on household composition and characteristics of each member (age, gender, and education). The health development army (HDA) volunteers are cadres of women within a community that support and extend the field-related activities of HEWs. HDAs are comprised of up to 30 households (HH) in the same neighborhood that meet in smaller groups of six members, commonly referred to as 1for5 networks. HDA team leaders, which oversee the 30 HHs, are selected by the members. The health development army team leaders (HDATL) questionnaire along with the other two frontline health worker questionnaires (HEW and ADA) was used to interview those working close to or in the community. These questionnaires aimed at assessing four major issues: (1) frequency of interactions between FLWs and mothers/caregivers and modes of interactions; (2) content of the interactions between FLWs and mothers/caregivers, especially discussions about IYCF messages and the time spent on IYCF-related discussions; (3) IYCF knowledge, workload and training and supervision received by FLWs; and (4) FLWs’ motivation and satisfaction about their jobs.